2002
DOI: 10.1177/002215540205001115
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Myosin Heavy Chain Isoforms Along Intrafusal Fibers of Rat Soleus Muscle Spindles After 14 Days of Hindlimb Unloading

Abstract: Morphological, contractile, histochemical, and electrophoretical characteristics of slow postural muscles are altered after hindlimb unloading (HU). However, very few data on intrafusal fibers (IFs) are available. Our aim was to determine the effects of 14 days of hindlimb unloading on the morphological and immunohistochemical characteristics of IF in rat soleus muscle. Thirty-three control and 32 unloaded spindles were analyzed. The number and distribution of muscle spindles did not appear to be affected afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 50 publications
4
14
0
Order By: Relevance
“…Instead, they were mostly unstained or occasionally stained weakly to moderately, indicating a significant reduction in the My-HC ␣ -c content in the aged nuclear bag 1 and bag 2 fibers. A similar reduction has also been observed in rat nuclear bag 1 fibers after neonatal and adult deefferentation (Pedrosa et al 1990;Walro et al 1997;Wang et al 1997) and in both nuclear bag 1 and bag 2 fibers after a 14-day period of hypogravity (De-Doncker et al 2002). In contrast to the nuclear chain fibers in young adult biceps, some nuclear chain fibers in old muscle spindles showed novel expression of MyHC␣-c isoform.…”
Section: Alterations In Myhc Compositionsupporting
confidence: 75%
“…Instead, they were mostly unstained or occasionally stained weakly to moderately, indicating a significant reduction in the My-HC ␣ -c content in the aged nuclear bag 1 and bag 2 fibers. A similar reduction has also been observed in rat nuclear bag 1 fibers after neonatal and adult deefferentation (Pedrosa et al 1990;Walro et al 1997;Wang et al 1997) and in both nuclear bag 1 and bag 2 fibers after a 14-day period of hypogravity (De-Doncker et al 2002). In contrast to the nuclear chain fibers in young adult biceps, some nuclear chain fibers in old muscle spindles showed novel expression of MyHC␣-c isoform.…”
Section: Alterations In Myhc Compositionsupporting
confidence: 75%
“…This is probably due to the presence of the capsule surrounding intrafusal fibers (Yellin and Eldred, 1970;Maier et al, 1972). In a study on the morphological and histochemical properties of intrafusal fibers after HU (De-Doncker et al, 2002), we have demonstrated that there was no significant difference in number, cross-sectional area and histochemical properties of intrafusal fibers in comparison with soleus muscle spindles of control rats. Moreover, in the rat soleus muscle, the number (HU: 13.5±1.3; CONT: 14.3±1.5) and length (HU: 2.75±0.2·mm; CONT: 2.82±0.3·mm) of muscle spindles were not changed after a HU period.…”
Section: During Humentioning
confidence: 79%
“…It is interesting to note that similar myosin heavy chain protein adaptations were found in rats in response to hind-limb unloading [18] and denervation [78,79]. The loss of nuclear chain fibers may impair the static sensitivity of the spindle and ultimately the ability to correctly interpret muscle length [33].…”
Section: Mechanisms Of Proprioception Deterioration With Agingmentioning
confidence: 80%